Characterization of adenovirus type 2 transcriptional complexes isolated from infected HeLa cell nuclei. - Wilhelm, J (1976)
HeLa cell nuclei, isolated 17 h after infection with human adenovirus type 2 (Ad2), were treated with 200 mM ammonium sulfate. The extract (S200 fraction) contained 50 to 70% of the nonintegrated Ad2 DNA, which was in the form of nucleoprotein complexes. These complexes contained native, intact Ad2 DNA (with the exception of replicative intermediates) and could be partially purified and resolved by velocity gradient centrifugation. Using high-salt (200 mM ammonium sulfate) incubation conditions, more than 95% of the nuclear RNA polymerase activity belonged to class B. About 45% of the class B enzyme molecules bound to DNA in the nuclei (those "engaged" in RNA synthesis) were released from the nuclei in the form of Ad2 transcriptional complexes by treatment with 200 mM ammonium sulfate. At least 90% of the RNA synthesized in high salt in the nuclei or in the S200 fraction was Ad2 specific, and essentially all of this RNA was complementary to the l strand of Ad2 DNA. These findings are compatible with what is known about Ad2-specific RNA synthesis in vivo. The analysis of the RNA synthesized from partially purified transcriptional complexes supports the contention that its transcription is almost entirely asymmetric, and that the asymmetry observed in vivo is not a consequence of the rapid degradation of h-strand transcripts. The RNA synthesized in vitro in the absence of detectable RNase activity sedimented with a maximum size of 35 to 40S. Less than 5% of the nuclear or the S200 fraction RNA polymerase activity was class C when assayed under non-reinitiating conditions. Although much of the RNA synthesized by the class C enzyme was Ad2 specific, 5.5S virus-associated RNA was not the predominant product. The isolation of Ad2 DNA transcriptional complexes provides an attractive system for further characterizing the Ad2 DNA template used for transcription and for studying the regulation of the expression of the Ad2 genome during the productive infection cycle.